Effect of Coal Particles on Embryonic Development, Egg Hatching Rate and Larvae Survival Rate of Climbing Perch Fish Anabas testudineus BLOCH - Pahmi Ansyari; Zairin Noor; Fatmawati; Emmy Sri Mahredha (Institute of Medico-legal Publications Pvt Ltd, 2021)
This study aimed to analyze the impact of coal particles on the embryo development, egg hatching rateand larvae survival rate of climbing perch fish Anabas testudineus Bloch. The research was done in the wetlaboratory of the Faculty of Fisheries and Marine, Lambung Mangkurat University for six months. Thetreatment in this study was a dose of coal particles exposure to eggs and larvae. The coal particles measuring150 ?m can penetrate the eggshell and interfere with embryo development at the stage of organ formation(organogenesis) and larval development. The eggs were exposed to coal particles 15 mg/litre of water. Itturns hatching rate was 87% lower than without exposure to 98%. Similarly, the larvae survival rate (up today 4) were exposed to coal dust 80% and without exposure to 93%.